Trade Policy Issues. (International Monetary Fund, 1997)
This book edited by Chorng-Huey Wong and Naheed Kirmani, examines a wide range of trade policy issues relevant in the 1990s that were the subject of a seminar organized by the IMF in 1996. The topics include the design and implementation of trade reform, trade liberalization in industrial and transition economies, regional trading arrangements, the impact of the Uruguay Round, the role of the World Trade Organization, and post Uruguay Round issues.